A comprehensive review on hazardous aspects and management strategies of electronic waste: Bangladesh perspectives. Issue 7 (July 2022) - Roy, Hridoy; Rahman, Tanzim Ur; Suhan, Md. Burhan Kabir; Al-Mamun, Md. Rashid; Haque, Shafaul; Islam, Md. Shahinoor
Abstract: Electronic waste (e-waste) contains a variety of electronic components e.g., metals, non-metals, plastics, cables, etc. The excessive generation of e-waste has become a significant concern in the last few decades. The current global e-waste generation is 57.4 million metric tons (MMT) per year. Asia produces the highest amount of e-waste (24.9 MMT) followed by America, Europe, Africa, and Oceania. In Bangladesh, e-waste produces from two sources: its own consumption of electronic devices, which is 0.6 MMT, and imported e-waste from ship breaking yards that is 2.5 MMT in 2021. However, inadequate information on the current state of e-waste generation and management systems in Bangladesh has created a void to establish the future direction for proper handling of e-waste. In this work, the Bangladesh perspective of e-waste has been analyzed. The environmental, health economical forfeiture of e-waste has been discussed. The development of government legislations regarding e-waste have been stated. The establishment of e-waste management has been designed by the life cycle assessment (LCA) and material flow analysis (MFA) models. Moreover, a holistic approach for understanding the possible hazards, the economic feasibility of e-waste processing and viable management models for e-waste in Bangladesh was endeavored in this work to propose systematic future directions and recommendations to improve the current e-waste scenario of Bangladesh. Graphical abstract: Image 1 Highlights: Collection, recycling, and disposal processes have to be established in Bangladesh. E-waste generation in Bangladesh is 3.1 MMT including shipbreaking yards generation. Bangladesh has an e-waste business potential of 221 million USD/yr. The policies and legislations for e-waste management in Bangladesh are not adequate. A combined MFA and LCA model can help decision-making for e-waste management. Abstract : e-waste generation; e-waste management; Health hazards; Material flow analysis; Life cycle assessment.